THE EFFECT OF PSYCHOLOGICAL CONTRACT VIOLATION ON THE SATISFACTION OF BASIC PSYCHOLOGICAL NEEDS - Indyastuti, Devani Laksmi (Journal of Management and Business, 2018)
This study aims to examine the effect of violations of psychological contracts on satisfaction of basic psychological needs. Basic psychological needs consist of a sense of autonomy, competency and connectedness. Data were obtained from a sample of teachers and staff in schools in Purwokerto. The research method used a survey. The results showed that it is important for school administrators to pay attention to the employee psychological violations. Based on the research results showed that psychological contract breach effects the autonomy and connectedness of a person, but not the competence.